IT GOVERNANCE EVALUATION USING COBIT 5 FRAMEWORK ON THE NATIONAL LIBRARY - Johanes Fernandes Andry; Ari Kurnia Setiawan (Jurnal Sistem Informasi, 2019)
National Library of Indonesia (NLI) is a public library located in Jakarta that was established in 1980 by the decree of Ministry of Education and Culture. This day NLI has already applied digitalization of its contents and its management with IT, IT has been an important aspect in an organization. The objective of IT implementation is to increase effectivity and performance in organization. In order to get maximum results good IT Governance is needed in order to align IT with business, the better IT Governance the greater outcome that the organization will get. The objective of this research is get an overview about the level of IT Governance on going, the analysis tool will be used is COBIT 5 focusing on DSS domain. The average score of DSS01, DSS02 and DSS 03 is in 1.2 to 1.6 and for the DSS04, DSS05 and DSS06 domain the average score is between 2.1 and 2.4